2002
DOI: 10.1128/jvi.76.23.11845-11852.2002
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of the Murine Leukemia Virus Envelope Protein Is Critical for Lipid Raft Association and Surface Expression

Abstract: To investigate the association of the murine leukemia virus (MuLV) Env protein with lipid rafts, we compared wild-type and palmitoylation-deficient mutant Env proteins by using extraction with the mild detergent Triton X-100 (TX-100) followed by a sucrose gradient flotation assay. We found that the wild-type MuLV Env protein was resistant to ice-cold TX-100 treatment and floated to the top of the gradients. In contrast, we observed that the palmitoylation-deficient mutant Env protein was mostly soluble when ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 42 publications
1
59
0
Order By: Relevance
“…Such differences have been observed, for instance, between influenza viruses and retroviruses. When acylation of the envelope glycoproteins of retroviruses was abolished, surface transport and incorporation into virions were reduced with a concomitant loss in infectivity (21,34,39). On the other hand, there is no evidence that acylation affects the fusion property of the retrovirus envelope glycoprotein, again in contrast to the case for influenza virus HAs of subtypes H1, H2, and H7.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Such differences have been observed, for instance, between influenza viruses and retroviruses. When acylation of the envelope glycoproteins of retroviruses was abolished, surface transport and incorporation into virions were reduced with a concomitant loss in infectivity (21,34,39). On the other hand, there is no evidence that acylation affects the fusion property of the retrovirus envelope glycoprotein, again in contrast to the case for influenza virus HAs of subtypes H1, H2, and H7.…”
Section: Discussionmentioning
confidence: 68%
“…In particular, quite a comprehensive picture on the contribution of DIG domains to the biology of retroviruses has evolved in recent years. It was shown that covalently bound lipids promote the association of the viral Gag and envelope proteins with DIG domains of the plasma membrane (21,39) and that this association plays a critical role not only for the assembly and release of virus particles (23,32,37), but also for virus entry into the host cell (10).…”
Section: Discussionmentioning
confidence: 99%
“…We next tested whether gPr80 gag might facilitate M-MuLV release through cholesterol-rich plasma membrane subdomains, also called lipid rafts. HIV buds through lipid rafts (18,19), and this process has also been reported for MuLV (20,21). BST-2 localizes in lipid rafts (22), so IFN induction of BST-2 would be expected to efficiently inhibit release of virions budding through lipid rafts, whereas it would be expected to have less effect on virus released independent of lipid rafts.…”
mentioning
confidence: 99%
“…For instance, palmitoylation-deficient Env mutants of murine leukemia virus (MLV) are mostly soluble when extracted using ice-cold Triton X-100, and they stay at the bottom of the sucrose gradient (28). In addition, treatment of cells with ␤-methyl cyclodextrin abolishes the ability of the MLV Env to associate with lipid rafts (28).…”
mentioning
confidence: 99%